Wykonaj działania :
a) 3x + 4x = ...
b) 5a + a = ...
c) 8y - 3y =
d) 10a - a = ...
e) 5x + (-7x) = ...
f) 2a - 6a = ...
g) -3b - 4b = ...
h) 3x + 2x + 7x = ...
i) 9y + 6y - 2y = ...
j) 5x - 4x + 2x = ...
k) 4a - trzy drugie a - pięć drugich a = ...
l) 4w - 6w - w = ...
m) -z + 8z - 5z = ...
n) - ⅖ c - c + ⅗ c = ...

3

Odpowiedzi

2010-03-06T19:47:24+01:00
3x + 4x =7x
5a + a = 6a
8y - 3y = 5y
10a-a=9a
5x + (-7x) =-2x
2a - 6a =-4a
-3b - 4b =-7b
3x + 2x + 7x=12x
9y + 6y - 2y=13y
k)0
l) 4w - 6w - w = -3w
-z + 8z - 5z =2z
- ⅖ c - c + ⅗ c=-4/5
Najlepsza Odpowiedź!
2010-03-06T19:47:43+01:00
A) 3x + 4x = 7x
b) 5a + a = 6a
c) 8y - 3y = 5y
d) 10a - a = 9a
e) 5x + (-7x) = -2x
f) 2a - 6a = -4a
g) -3b - 4b = -7b
h) 3x + 2x + 7x = 12x
i) 9y + 6y - 2y = 13y
j) 5x - 4x + 2x = 3x
k) 4a - trzy drugie a - pięć drugich a = 0a
l) 4w - 6w - w = -3w
m) -z + 8z - 5z = 2z
n) - ⅖ c - c + ⅗ c = -⅘c
2 5 2
2010-03-06T20:06:17+01:00
A) 3x + 4x = 7x
b) 5a + a = 6a
c) 8y - 3y = 5y
d) 10a - a = 9a
e) 5x + (-7x) = -2x
f) 2a - 6a = -4a
g) -3b - 4b = -7b
h) 3x + 2x + 7x = 12x
i) 9y + 6y - 2y = 13y
j) 5x - 4x + 2x = 3x
k) 4a - 3/2 a - 5/2 a = 0
l) 4w - 6w - w = -3w
m) -z + 8z - 5z = 2z
n) - ⅖ c - c + ⅗ c = -⅘c